Optical Rectennae: High Performance Multiwall Carbon Nanotube–Insulator–Metal Tunnel Diode Arrays for Optical Rectification (Adv. Electron. Mater. 3/2018). (9th March 2018) - Anderson, Erik C.; Bougher, Thomas L.; Cola, Baratunde A.
Abstract : The cover depicts the first air‐stable optical rectenna, using an array of carbon nanotube to convert red light to electricity. The device reported by Baratunde A. Cola and co‐workers manipulates electron tunneling in the diode by incorporating multiple dielectric layers, ultimately leading to a 10‐fold increase in efficiency.